Making Sense of Sensemaking: Conceptualising How Child and Family Social Workers Process Assessment Information. Issue 2 (2nd April 2020) - Cook, Laura; Gregory, Mark
ABSTRACT: This article offers a new conceptualisation of sensemaking in social work assessment. During assessment, social workers are required to make sense of a wide range of information. This may include written reports, behavioural cues, verbal, sensory and emotional data. In this article, the term "sensemaking" is used to refer to the processes through which social workers gather, select and interpret this varied, and often incomplete, information during assessment. Sensemaking is defined as a psychosocial process which precedes and underpins professional judgement and decision-making. While there has been interest in how social workers assess risk to children, the sensemaking process that occurs before a decision is made has received less attention, and sensemaking lacks a clear definition. Drawing on existing research on assessment and theoretical literature from the fields of psychology and organisational studies, this article offers a view of sensemaking through three lenses: sensemaking as intuitive process, sensemaking as social storytelling and sensemaking as an emotionally-informed process . Drawing together key features from these three perspectives, we advance six propositions about sensemaking in child and family assessment: (1) sensemaking is a process of formulation; (2) sensemaking involves movement between conscious and non-conscious processes; (3) sensemaking can be developed through experience and learning through reflection; (4) sensemaking is inseparable from the environment in which it takes place (5) sensemaking is a dialogic process; (6) sensemaking is an emotionally-informed as well as cognitive process. The article concludes with the implications of this conceptualisation of sensemaking for assessment in child and family social work.